Weave of absence - Martin, Carol Ann (Mystery story writer) (Martin, Carol Ann (Mystery story writer). Weaving mystery., 2014)
It's a joyous time at Dream Weaver-Della Wright's studio in small-town Briar Hollow, North Carolina- as Marnie Potter, part-time employee and full-time friend, is preparing for her upcoming marriage. Della has enlisted a tight-knit group of close friends to handweave a beautiful collection of fine household linens as a wedding gift for the happy couple. But when Della notices Marnie's suave fiance engaged in a heated argument with one of her students at the engagement party, she starts to worry that there may be something wrong with Marnie's Mr. Right. After the student turns up dead the next day, Della must weave together the clues to find the killer-before Marnie agrees to "til death do us part."